Analisis User Interface Dengan Metode User Centered Design Pada Aplikasi Sukun - Pelealu , Cynthia Gloria; Mukhayaroh , Anna (Journal of Students‘ Research in Computer Science, 2023)
As the times progress, technology advances so that a media or hardware device is created to communicate and search for news information such as computers, mobile phones or smartphones, and others. Then he also made a software to make it easier for us to find information and communicate. One form of software is an application. There are several kinds of applications that provide various services and features, such as game applications (games), social media applications, and other application services. But in addition to the many applications there are still many that are lacking in terms of interface, so many users find it difficult to use the application. One of them is the Sukun application. This application is used by hundreds of congregations at the Indonesian Bible Mission Fellowship Church (GPMII). But because this application is still in the development stage so there are still many shortcomings in displaying the user interface, therefore in this study the authors apply the User Centered Design (UCD) method to this application to display an increasingly better interface.